Evaluation of Genotoxic Potential of 2-(Bromoacetamido) Phenylboronic Acid on Balb/C Mice Peripheral Blood Cells Using In Vivo Micronucleus Assay - Khalil, Ahmad; Salman, Wala; AlQaoud, Khaled (Jordan Journal of Pharmaceutical Sciences, 2017)
Boronic acids and their ester derivatives are important compounds in medicinal chemistry. Most boronic acids present no particular toxicity compared to other organic compounds. Despite of this promising sign and the recognition of the therapeutic potential of some boronic acid derivatives by the US Food and Drug Administration, medical applications of these compounds are still restricted due to lack of complete toxicity profile. A novel phenylboronic acid derivative; 2-(bromoacetamido) phenylboronic acid (2-BAPBA) has been recently prepared. In this study, we examined capacity of 2-BAPBA to cause DNA damage in erythrocytes of mice expressed as micronuclei (MN). The test chemical (2-BAPBA) was dissolved to homogeneity in 50% in dimethyl sulfoxide and solution was used at varying doses. The 24h i. p. LD50 of 2-BAPBA was estimated to be 20mg/kg. At the highest 2 doses; 80mg/kg and 100mg/kg of the test chemical, no animal survived. In contrast, no death or toxic symptoms were observed among animals received 5mg/kg and 10mg/kg. Reduced activity was observed in all mice treated with a dose ≥20mg 2-BAPBA /kg b. w. No significant changes in body weight were noted in all mice groups. The increases in percent of micronucleated polychromatic erythrocytes and decreases in percent polychromatic erythrocytes, at doses ranging between 5mg/kg and 35mg/kg for 48 and 72h, were statistically significant (P<0.01) compared with parallel control group. The results suggest that the compound, under present experimental conditions, is cytotoxic and genotoxic. To reach more definitive conclusions about this subject, further research with different test systems is needed